2016
DOI: 10.3947/ic.2016.48.1.54
|View full text |Cite
|
Sign up to set email alerts
|

The 2015 Clinical Guidelines for the Treatment and Prevention of Opportunistic Infections in HIV-Infected Koreans: Guidelines for Opportunistic Infections

Abstract: The Committee for Clinical Guidelines for the Treatment and Prevention of Opportunistic Infections of the Korean Society for AIDS was founded in 2011. The first edition of the Korean guidelines was published in 2012. The guideline recommendations contain important information for physicians working with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) in the clinical field. It has become necessary to revise the guidelines due to new data in this field. These guidelines aim to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The guidelines also favor treatment of HIV-positive patients whose infection status is acute or who were recently infected [ 12 ]. Although previous clinical data and guidelines recommend early initiation of ART, most HIV-infected patients initiate ART when they are diagnosed with low CD4+ cell counts [ 2 13 14 ]. In Korea, the total number of patients infected with HIV in 2015 was 10,502 and there were 1,052 newly infected patients; incidence has been observed to be increasing steadily.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines also favor treatment of HIV-positive patients whose infection status is acute or who were recently infected [ 12 ]. Although previous clinical data and guidelines recommend early initiation of ART, most HIV-infected patients initiate ART when they are diagnosed with low CD4+ cell counts [ 2 13 14 ]. In Korea, the total number of patients infected with HIV in 2015 was 10,502 and there were 1,052 newly infected patients; incidence has been observed to be increasing steadily.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies showed that poor adherence to medication led to failure of viral suppression and poor recovery of CD4+ T cells [ 1 , 2 ]. Poor adherence causes low CD4+ cell levels and low CD4+ cell levels are obviously associated with opportunistic infections [ 3 ]. In addition, treatment failure due to poor adherence can mislead physicians, resulting in an unnecessary change of ART [ 4 ].…”
mentioning
confidence: 99%
“…Lymph nodes (LNs) are commonly affected sites in extrapulmonary tuberculosis. The treatment of tuberculous (TB) lymphadenopathy (LAP) is not usually different from that of pulmonary TB, typically consisting of a six-month anti-tuberculosis regimen [ 1 2 ]. The decrease in LN size is usually used as an indicator of treatment response in TB LAP, while negative conversion of sputum culture is used to determine treatment response in pulmonary TB.…”
mentioning
confidence: 99%